Peran Tanah dalam Administrasi Pemerintahan: Tinjauan Yuridis dan Manajerial di Indonesia - Zaenal, Abdil Rahman; Isnayani, Isnayani (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
Land has a strategic function in the government administration system, both as an economic resource and as an object of law and regional governance. This journal discusses the importance of land management in public administration, covering aspects of land law, management of state-owned land assets, agrarian conflicts, and digitization of land information systems. The research was conducted through literature studies and legal analysis of regulations such as the Basic Agrarian Law, the Job Creation Law, and the Head of the National Land Agency Regulation. The results of the study show that inaccuracies in land administration are the main causes of overlapping ownership and agrarian conflicts. Therefore, digital and participatory-based land administration reform is urgently needed.